Evaluation method for cyclic adsorption performance of carbon dioxide adsorbent

Through thermogravimetric analysis method and curve fitting technology, the problem of lack of standard evaluation methods in the existing technology is solved, and the systematic and standardized evaluation of the circulation performance of carbon dioxide adsorbents is achieved.

CN119688524AActive Publication Date: 2025-03-25CHINA ENERGY INVESTMENT CORP LTD +1

Patent Information

Application Number
CN202311247663.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-03-25
Estimated Expiration
2043-09-25

AI Technical Summary

Technical Problem

The prior art lacks the accurate definition, formula description and scope of application of physical quantities used for cyclic adsorption performance of carbon dioxide adsorbents, and it is difficult to conduct unified standards evaluation.

Method used

A cyclic adsorption performance evaluation method is provided. Multiple adsorption and desorption tests are performed through a thermogravimetric analyzer to calculate the regeneration rate and adsorption quantity change rate of the adsorbent, and fit the curve function to evaluate the adsorbent performance.

Benefits of technology

A relatively standard evaluation method based on thermogravimetric analysis testing has been established. It can select appropriate parameters according to actual conditions, conduct qualitative analysis of various adsorbents, and select suitable adsorbents, with a large range of use and strong applicability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119688524A_ABST
    Figure CN119688524A_ABST
Patent Text Reader

Abstract

The invention relates to a method for evaluating the cyclic adsorption performance of a carbon dioxide adsorbent, which comprises the following steps: S1, performing multiple adsorption and desorption tests on a to-be-tested adsorbent after impurity removal treatment in a thermogravimetric analyzer to obtain a thermogravimetric cycle curve; s2, parameters E1, F1, Hi and Ii are obtained according to the thermogravimetric cycle curve and a formula; s3, obtaining a first fitting curve and a second fitting curve; s4, evaluating the performance of the adsorbent to be tested according to one or more of E1, Ei, H2, I2, F1, Fi, the first fitting curve function and the second fitting curve function. By adopting the method, a relatively standard evaluation method for evaluating the performance of the adsorbent based on the thermogravimetric analysis test can be established, a plurality of adsorbents can be qualitatively analyzed by selecting proper parameters according to actual use conditions, proper adsorbents are selected by comparing qualitative analysis results, and the method is wide in use range and high in applicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of carbon dioxide adsorption, and in particular, to a method for evaluating the cyclic adsorption performance of a carbon dioxide adsorbent. Background Art

[0002] At present, the use of fossil fuels and industrial hydrogen production can produce a large amount of CO 2 , which aggravates the greenhouse effect. Therefore, the capture, storage and conversion of carbon dioxide have gradually become the focus of greenhouse gas emission reduction and control. In recent years, the adsorption and desorption cycle reaction of calcium-based adsorbents to separate CO 2 This method has aroused great interest and extensive research among scholars from various countries.

[0003] Literature (Preparation of coated modified nano calcium carbonate and CO 2 Cyclic Adsorption Performance, Wang Yan, Zhejiang University, 2014), this study used a thermogravimetric analyzer to evaluate the adsorption and cyclic performance of the modified nano-calcium carbonate adsorbent, proposed parameters for qualitative and quantitative analysis of the cyclic stability of the adsorbent: adsorption capacity and decay rate, and defined the calculation method of the parameters, which were applied to the analysis of the modified adsorbent. 2 Screening of calcium-based precursor materials for the preparation of CaO, Zhang Mingming et al., Science China: Chemistry, 2012). This study used natural calcium sources and chemical reagents to prepare CaO materials, evaluated the adsorption capacity and long-term cycle stability of CaO using a thermogravimetric analyzer, and proposed new physical quantities for calculating and evaluating adsorption capacity.

[0004] In the prior art, a thermogravimetric analyzer is used to test the long-term cycle stability of the prepared adsorbent material, and new parameters for evaluation and analysis are defined. The new parameters and traditional existing parameters are used to describe and evaluate the cycle performance. The description and evaluation mostly use qualitative descriptions, and lack accurate definitions of the physical quantities used in the evaluation, formula descriptions, and applicable scopes, making it difficult to use them to evaluate different types of adsorbents in a unified standard. Summary of the invention

[0005] The purpose of the present disclosure is to provide a method for evaluating the cyclic adsorption performance of a carbon dioxide adsorbent, so as to solve the problems in the prior art of lacking accurate definition, formula description and applicable scope of the physical quantities used for evaluation, and being difficult to use for unified standard evaluation of different types of adsorbents.

[0006] In order to achieve the above object, the present invention provides a CO 2 A method for evaluating the cyclic adsorption performance of an adsorbent, the method comprising:

[0007] S1, subjecting the adsorbent to be tested to a desorption treatment in a thermogravimetric analyzer and then to multiple adsorption and desorption tests to obtain a thermogravimetric cycle curve;

[0008] S2. Calculate the regeneration rate H of the adsorbent in the i-th adsorption and desorption test according to formula 1 i , in %:

[0009]

[0010] Among them, E 1 is the weight percentage of the adsorbent after desorbing impurities in the first adsorption-desorption test, in wt%; E i is the desorption of CO in the i-th adsorption and desorption test 2 The weight percentage of the adsorbent to be tested is expressed in wt%;

[0011] According to formula 2, the adsorption amount change rate I of the adsorbent in the i-th adsorption and desorption test is calculated. i , in %:

[0012]

[0013] Among them, F 1 is the CO adsorbed by the adsorbent to be tested in the first adsorption-desorption test 2 The weight of the adsorbent to be tested is expressed as a percentage of the weight of the adsorbent to be tested, in wt%; F i is the CO adsorbed by the adsorbent in the i-th adsorption-desorption test 2 The weight percentage of the adsorbent to be tested is expressed in wt%;

[0014] S3, the regeneration rate H of all adsorption and desorption tests i and the corresponding number of cycles i to form a first data set; fitting the first data set to obtain a first fitting curve function H=f(i); and setting the adsorption amount change rate I during all the adsorption and desorption tests i and the corresponding number of cycles i to form a second data set; fitting the second data set to obtain a second fitting curve function I=f(i);

[0015] S4. According to E 1 、E i 、F 1 、F i , H 2 ,I 2 , one or more of the first fitting curve function and the second fitting curve function to evaluate the performance of the adsorbent to be tested; the i is a positive integer and i≥2.

[0016] Optionally, according to H 2The adsorbent stability of the adsorbent to be tested is evaluated using the first fitting curve function.

[0017] Optionally, according to I 2 The adsorption stability of the adsorbent to be tested is evaluated with a second fitting curve function.

[0018] Optionally, according to F 1 and F i The adsorption capacity of the adsorbent to be tested is evaluated.

[0019] Optionally, the adsorption-desorption test is performed more than 5 times.

[0020] Optionally, the evaluation method further comprises: S5, calculating the change J of the adsorption amount of the adsorbent to be tested in two adjacent adsorption and desorption tests according to Formula 3 i , in wt%:

[0021] J i =F i-1 -F i ; Formula 3

[0022] Among them, F i-1 is the CO adsorbed by the adsorbent in the i-1th adsorption-desorption test 2 The weight percentage of the adsorbent to be tested, i is a positive integer and i≥2; when the change in adsorption amount J i <0, indicating that the adsorption performance of the adsorbent to be tested in the i-th adsorption-desorption test is improved compared with that in the i-1-th adsorption-desorption test; when the change in adsorption amount J i >0, indicating that the adsorption performance of the adsorbent to be tested in the i-th adsorption-desorption test is lower than that in the i-1-th adsorption-desorption test.

[0023] Optionally, the adsorption-desorption test comprises: subjecting the adsorbent after impurities are removed to a CO-rich adsorbent at an adsorption temperature. 2 The adsorbent is contacted with the gas for adsorption treatment; until the weight of the adsorbent after impurities are removed is stable, thereby obtaining a carbon-rich adsorbent; and the carbon-rich adsorbent is regenerated at a regeneration temperature until the weight of the carbon-rich adsorbent is stable, thereby obtaining a regenerated adsorbent.

[0024] Optionally, the evaluation method further comprises calculating the limit cycle number x when the adsorbent to be tested fails completely according to Formula 4: 2 :

[0025] I(i)=0; Formula 4

[0026] x 2 The larger the value is, the longer the maximum life of the adsorbent to be tested is.

[0027] Optionally, the evaluation method further includes: 2 The maximum cycle number M of the adsorbent to be tested is obtained by rounding; the larger the value of the maximum cycle number M is, the larger the maximum cycle number of the adsorbent to be tested is.

[0028] The application of the evaluation method described in the first aspect of the present disclosure in the field of carbon dioxide adsorption.

[0029] Through the above technical scheme, the thermogravimetric cycle curve obtained by thermogravimetric analysis is used, and the weight percentage E of the adsorbent after desorbing impurities in the first adsorption-desorption test is obtained according to the thermogravimetric cycle curve. 1 and the CO adsorbed by the adsorbent to be tested 2 The weight of the adsorbent to be tested is the percentage of the weight of 1 In the i-th adsorption and desorption test, the desorbed CO 2 The weight percentage of the adsorbent after the test is E i and the CO adsorbed by the adsorbent to be tested 2 The weight of the adsorbent to be tested is the percentage of the weight of i , and the above parameters are defined in detail, and the regeneration rate of the adsorbent H is calculated by the calculation formula i and adsorption amount change rate I i , and then according to the regeneration rate of the adsorbent H i and adsorption amount change rate I i The mathematical model is fitted to obtain the first fitting curve and the second fitting curve; the performance of the adsorbent is evaluated according to the parameters and fitting curves defined in detail. The above method can establish a relatively standard evaluation method for evaluating the performance of the adsorbent based on thermogravimetric analysis. According to the actual use, appropriate parameters can be selected to perform qualitative analysis on a variety of adsorbents. By comparing the qualitative analysis results, the appropriate adsorbent can be selected, which has a wide range of use and strong applicability.

[0030] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0032] Figure 1 It is a thermogravimetric cycle curve adopted by a method for evaluating the cyclic adsorption performance of a carbon dioxide adsorbent disclosed in the present invention. DETAILED DESCRIPTION

[0033] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.

[0034] The present invention provides a CO 2 A method for evaluating the cyclic adsorption performance of an adsorbent, the method comprising:

[0035] S1, subjecting the adsorbent to be tested to a desorption treatment in a thermogravimetric analyzer and then to multiple adsorption and desorption tests to obtain a thermogravimetric cycle curve;

[0036] S2. Calculate the regeneration rate H of the adsorbent in the i-th adsorption and desorption test according to formula 1 i , in %:

[0037]

[0038] Among them, E 1 is the weight percentage of the adsorbent after desorbing impurities in the first adsorption-desorption test, in wt%; E i is the desorption of CO in the i-th adsorption and desorption test 2 The weight percentage of the adsorbent to be tested is expressed in wt%;

[0039] According to formula 2, the adsorption amount change rate I of the adsorbent in the i-th adsorption and desorption test is calculated. i , in %:

[0040]

[0041] Among them, F 1 is the CO adsorbed by the adsorbent to be tested in the first adsorption-desorption test 2 The weight of the adsorbent to be tested is expressed as a percentage of the weight of the adsorbent to be tested, in wt%; F i is the CO adsorbed by the adsorbent in the i-th adsorption-desorption test 2 The weight percentage of the adsorbent to be tested is expressed in wt%;

[0042] S3, the regeneration rate H of all adsorption and desorption tests i and the corresponding number of cycles i to form a first data set; fitting the first data set to obtain a first fitting curve function H=f(i); and setting the adsorption amount change rate I during all the adsorption and desorption tests i and the corresponding number of cycles i to form a second data set; fitting the second data set to obtain a second fitting curve function I=f(i);

[0043] S4. According to E 1 、E i、F 1 、F i , H 2 ,I 2 , one or more of the first fitting curve function and the second fitting curve function to evaluate the performance of the adsorbent to be tested; the i is a positive integer and i≥2.

[0044] Through the above technical scheme, the thermogravimetric cycle curve obtained by thermogravimetric analysis is used, and the weight percentage E of the adsorbent after desorbing impurities in the first adsorption-desorption test is obtained according to the thermogravimetric cycle curve. 1 and the CO adsorbed by the adsorbent to be tested 2 The weight of the adsorbent to be tested is the percentage of the weight of 1 In the i-th adsorption and desorption test, the desorbed CO 2 The weight percentage of the adsorbent after the test is E i and the CO adsorbed by the adsorbent to be tested 2 The weight of the adsorbent to be tested is the percentage of the weight of i , and the above parameters are defined in detail, and the regeneration rate of the adsorbent H is calculated by the calculation formula i and adsorption amount change rate I i , and then according to the regeneration rate of the adsorbent H i and adsorption amount change rate I i The mathematical model is fitted to obtain the first fitting curve and the second fitting curve; the performance of the adsorbent is evaluated according to the parameters and fitting curves defined in detail. The above method can establish a relatively standard evaluation method for evaluating the performance of the adsorbent based on thermogravimetric analysis. According to the actual use, appropriate parameters can be selected to perform qualitative analysis on a variety of adsorbents. By comparing the qualitative analysis results, the appropriate adsorbent can be selected, which has a wide range of use and strong applicability.

[0045] In one embodiment, the evaluation of the adsorbent disclosed herein can be qualitatively analyzed from the perspective of stability and adsorption amount, and stability includes adsorbent stability and adsorption amount stability. In this embodiment, adsorbent stability refers to the change in weight of the adsorbent after impurities are removed in an adsorption-desorption test; when the change in the weight of the adsorbent is small, it means that the adsorbent stability is good, otherwise it means that the adsorbent stability is poor. Adsorption amount stability refers to the change in the amount of carbon dioxide absorbed by the adsorbent in an adsorption-desorption test; when the change in the amount of carbon dioxide absorbed is small, it means that the adsorption amount stability is good, otherwise it means that the adsorption amount stability is poor.

[0046] In one embodiment, when both the adsorbent stability and the adsorption amount stability of the adsorbent are good, it indicates that the stability of the adsorbent is good.

[0047] In one implementation, step S4 further includes:

[0048] S41. According to H 2 evaluating the adsorbent stability of the adsorbent to be tested using the first fitting curve function;

[0049] S42. According to I 2 and evaluating the adsorption stability of the adsorbent to be tested using a second fitting curve function;

[0050] S43, according to F 1 and F i The adsorption capacity of the adsorbent to be tested is evaluated.

[0051] Among them, the specific evaluation method of the adsorbent stability of the adsorbent to be tested includes:

[0052] S411, determining the line type of the first fitting curve: when the line type of the first fitting curve is closer to a straight line, it means that the weight change of the adsorbent to be tested is more uniform;

[0053] S412, determining the slope of the approximate straight line. When the slope of the approximate straight line is closer to 0, the adsorbent stability of the adsorbent to be tested is better.

[0054] S413, judge H 2 When the H 2 The closer it is to 100%, the better the adsorbent stability of the adsorbent to be tested is.

[0055] Among them, the specific evaluation method of the adsorption stability of the adsorbent to be tested includes:

[0056] S421, determining the line type of the second fitting curve: when the line type of the second fitting curve is closer to a straight line, it means that the adsorption amount of the adsorbent to be tested changes more evenly;

[0057] S422, determining the slope of the approximate straight line. When the slope of the approximate straight line is closer to 0, the adsorption stability of the adsorbent to be tested is better.

[0058] S423, Judgment I 2 Value, when I 2 The closer it is to 100%, the better the adsorption stability of the adsorbent to be tested.

[0059] Among them, according to F 1 and F i The specific evaluation method for evaluating the adsorption amount of the adsorbent to be tested includes:

[0060] S43, F 1 and F iand the corresponding number of cycles i to form a third data set; plot the third data set to obtain an adsorption amount line graph; and judge the adsorption amount of the adsorbent according to the adsorption amount line graph.

[0061] In a specific embodiment, the adsorbent A and the adsorbent B to be tested are evaluated using steps S1 to S3 to obtain the following parameters: E of the adsorbent A to be tested during the first adsorption and desorption test; 1 The value is E 1A and E 1B ; E during the i-th adsorption-desorption test i The value is E iA and E iB ; F during the first adsorption-desorption test 1 The value is F 1A and F 1B ; F during the i-th adsorption and desorption test i The value is F iA and F iB ; The regeneration rate of the adsorbent in the second adsorption-desorption test H 2 Counted as H 2A and H 2B ; The adsorption rate of the adsorbent in the second adsorption-desorption test is 2 Counted as I 2A and I 2B ; and obtain a first fitting curve function and a second fitting curve function; and adopt step S4 to evaluate the adsorption performance of the adsorbent A to be tested and the adsorbent B to be tested:

[0062] S41. Evaluate the adsorbent stability of the adsorbent to be tested:

[0063] S411, comparing the line types of the first fitting curves of the adsorbent A to be tested and the adsorbent B to be tested, when one of the two is closer to a straight line, it indicates that the weight change of the adsorbent to be tested is more uniform;

[0064] S412, when the line types of the first fitting curves of the adsorbent A to be tested and the adsorbent B to be tested are both close to straight lines, the slopes of the approximate straight lines of the two are compared. When one of the slopes of the approximate straight lines of the two is closer to 0, it indicates that the adsorbent stability of the adsorbent to be tested is better;

[0065] S413, when the slopes of the first fitting curves of the adsorbent A to be tested and the adsorbent B to be tested are equal, compare the H 2A and H 2B , when H 2A Greater than H 2B When H 2A Less than H 2BThis indicates that the adsorbent stability of the adsorbent A is worse than that of the adsorbent B.

[0066] S42. Evaluate the adsorption stability of the adsorbent to be tested:

[0067] S421, comparing the line types of the second fitting curves of the adsorbent A to be tested and the adsorbent B to be tested, when one of the two is closer to a straight line, it indicates that the adsorption amount of the adsorbent to be tested changes more uniformly;

[0068] S422. When the line types of the second fitting curves of the adsorbent A and the adsorbent B are close to straight lines, the slopes of the approximate straight lines are compared. When one of the slopes of the approximate straight lines is closer to 0, it indicates that the adsorption amount stability of the adsorbent to be tested is better.

[0069] S423, when the slopes of the second fitting curves of the adsorbent A to be tested and the adsorbent B to be tested are equal, compare the I 2A and I 2B , when I 2A Greater than I 2B When I 2A Less than I 2B This indicates that the adsorption stability of the adsorbent A is worse than that of the adsorbent B.

[0070] S43, according to F 1 and F i Evaluate the adsorption capacity of the adsorbent to be tested: The F 1A 、F iA 、F 1B 、F iB and the corresponding cycle number i form a third data set; plotting the third data set to obtain a line graph of adsorption amount;

[0071] When the line graph of the adsorbent A to be tested is above the line graph of the adsorbent B to be tested, it means that the adsorption amount of the adsorbent A to be tested is better than that of the adsorbent B to be tested;

[0072] When the line graph of the adsorbent A to be tested is below the line graph of the adsorbent B to be tested, it means that the adsorption amount of the adsorbent A to be tested is worse than that of the adsorbent B to be tested.

[0073] In the above embodiment, when evaluating the catalyst to be tested, the technician can select appropriate data to compare multiple adsorbents according to specific usage requirements. For example, without considering the adsorbent stability and the adsorption amount stability, the adsorbent with the best adsorption amount in the 5th adsorption-desorption test can use the evaluation method of step S43 to perform qualitative analysis on multiple adsorbents to be tested, so as to select a better adsorbent that meets the requirements.

[0074] The adsorbent to be tested used in the present disclosure can be selected from solid adsorbents for carbon dioxide, and the solid adsorbent used can adsorb carbon dioxide by physical adsorption or chemical adsorption.

[0075] In one embodiment, the method for removing impurities from the adsorbent to be tested disclosed herein is a conventional method in the art, and the present application does not make any special requirements. For example, the impurity removal treatment includes: subjecting the adsorbent to be tested to a high temperature treatment under an inert atmosphere until the weight of the adsorbent to be tested is stabilized, thereby obtaining the adsorbent to be tested with impurities removed; wherein the inert atmosphere used for the impurity removal treatment is selected from nitrogen and / or argon.

[0076] The adsorption and desorption test disclosed in the present invention is a conventional method in the art, specifically comprising: allowing the impurity removal adsorbent to react with a CO-rich adsorbent at an adsorption temperature. 2 The adsorption treatment is carried out by contacting the impurity-removing adsorbent with the gas; until the weight of the impurity-removing adsorbent is stable, thereby obtaining a carbon-rich adsorbent; and the carbon-rich adsorbent is regenerated at a regeneration temperature, until the weight of the carbon-rich adsorbent is stable, thereby obtaining a regenerated adsorbent.

[0077] The method for forming the thermogravimetric cycle curve in the present disclosure is a conventional choice in the art, and the specific data needs to be determined according to the actual test situation, such as Figure 1 As shown, the abscissa of the thermogravimetric cycle curve is time, in units of min, and the ordinate is weight percentage and temperature, in units of wt% and °C, respectively; wherein the ordinate means the ratio of the real-time weight of the adsorbent in the thermogravimetric analyzer to the adsorbent to be tested. In this embodiment, the trend of the adsorbent changing with temperature and time can be obtained, and the required parameters can be more easily obtained from the thermogravimetric cycle curve, for example, the parameter can be the weight percentage E of the adsorbent after desorbing impurities in the first adsorption-desorption test to the adsorbent to be tested. 1 In the first adsorption-desorption test, the CO adsorbed by the adsorbent to be tested 2 The weight of the adsorbent to be tested is the percentage of the weight of 1 In the i-th adsorption and desorption test, the desorbed CO 2 The weight percentage of the adsorbent after the test is E i and CO adsorbed by the adsorbent in the i-th adsorption / desorption test 2The weight percentage of the adsorbent to be tested is F i .

[0078] A specific implementation mode, the present disclosure is based on Figure 1 The method for obtaining parameters from the thermogravimetric cycle curve shown in the figure includes: the curve of section A in the figure represents the impurity removal process. Specifically, the adsorbent removes water and impurities contained in the adsorbent in the thermogravimetric analyzer. Therefore, the weight of the adsorbent gradually decreases until the water and impurities in the adsorbent are completely removed and the weight reaches a stable value; at this time, the value of the stable section in the curve of section A is the weight percentage E of the adsorbent after desorbing impurities in the first adsorption and desorption test. 1 The curve of section B in the figure represents the adsorption process. Specifically, the temperature is lowered to the adsorption temperature and the inert atmosphere is switched to a CO-rich 2 gas, and to enable the adsorbent to be tested after impurity removal to adsorb rich CO at the adsorption temperature 2 CO in gas 2 , therefore, the weight gradually increases until the adsorbed CO 2 After saturation, the weight reaches stability. At this time, the difference between the values ​​of the curves of segment B and B that reach stability is the CO adsorbed by the adsorbent to be tested in the first adsorption and desorption test. 2 The weight of the adsorbent to be tested is the percentage of the weight of 1 The curve in section C in the figure represents the regeneration process. Specifically, the CO 2 The gas is switched to an inert atmosphere and the temperature is raised to the regeneration temperature to allow the carbon dioxide CO adsorbed in the carbon-rich adsorbent to 2 Therefore, the weight will gradually decrease until all carbon dioxide is desorbed and the weight reaches a stable value. At this time, the value when the C segment curve switches to the adsorption test is the value of the desorbed CO in the second adsorption and desorption test. 2 The weight percentage of the adsorbent after the test is E 2 In addition, the P segment curve in the figure represents the situation of the i-th adsorption and desorption test. At this time, the value of the P segment curve when switching to the adsorption test is E i The value of refers to the desorption of CO in the i-th adsorption and desorption test. 2 The weight percentage of the adsorbent after the test is expressed in wt%, and the difference between the values ​​of the curve that reaches stability F i It refers to the CO adsorbed by the adsorbent in the i-th adsorption and desorption test. 2 The weight percentage of the adsorbent to be tested is expressed in wt%. After the curve reaches stability, there may be some fluctuations, which should be regarded as normal. Small fluctuations generally do not affect the judgment trend.

[0079] In order to ensure the accuracy of the fitting curve function, the present disclosure needs to collect data from multiple cycles of adsorption and desorption tests, and the number of times cannot be too small. The present disclosure limits the number of the adsorption and desorption tests to more than 5 times, preferably more than 10 times, and more preferably more than 15 times.

[0080] The method disclosed in the present invention for fitting a mathematical model to the first data set and the second data set is a conventional method in the art. It should be noted that when selecting different types of fitting function types (straight line, parabola, exponential, etc.), the corresponding fitting degree R should be considered. 2 , to ensure the fitting degree R of the first fitting curve and the second fitting curve 2 Above 0.99, the goodness of fit R 2 Indicates the fitting effect of the curve and the actual data. The higher the fitting degree, the more accurate the fitting curve. In addition, there is a case where the fitting degree is poor. If the fitting degree R of the first fitting curve or the second fitting curve is 2 Less than 0.99, at this point, additional data can be added to improve the accuracy of mathematical model fitting.

[0081] In one embodiment, the evaluation method further comprises: S5, calculating the change J of the adsorption amount of the adsorbent to be tested in two adjacent adsorption and desorption tests according to Formula 3 i , in wt%:

[0082] J i =F i-1 -F i ; Formula 3

[0083] Among them, F i-1 is the CO adsorbed by the adsorbent in the i-1th adsorption-desorption test 2 The weight percentage of the adsorbent to be tested, i is a positive integer and i≥2; when the change in adsorption amount J i <0, indicating that the adsorption performance of the adsorbent to be tested in the i-th adsorption-desorption test is improved compared with that in the i-1-th adsorption-desorption test; when the change in adsorption amount J i >0, indicating that the adsorption performance of the adsorbent to be tested in the i-th adsorption-desorption test is lower than that in the i-1-th adsorption-desorption test.

[0084] The change in the adsorption amount of the adsorbent in the two adjacent adsorption and desorption tests J i A scatter plot is made with the corresponding cycle number i. When the J obtained from the i-th adsorption and desorption test i Value and the rest of J iWhen the values ​​differ greatly, an outlier is obtained, and it is judged according to the outlier whether it is caused by system error, test error or obvious failure of the adsorbent. In this embodiment, the outlier appearing in the i-th adsorption and desorption test is further judged whether the outlier is a measurement error; and then it is further judged whether the outlier that is not a measurement error is caused by obvious failure of the adsorbent to be tested or improvement of the cycle efficiency. In addition, the more times the outliers that are not measurement errors appear, the worse the adsorption stability of the adsorbent is.

[0085] In one embodiment, the evaluation method further includes calculating the limit cycle number x when the adsorbent to be tested fails completely according to Formula 4. 2 :

[0086] I(i)=0; Formula 4

[0087] x 2 The larger the value is, the longer the maximum life of the adsorbent to be tested is.

[0088] In a further embodiment, according to the limit cycle number x 2 Define the maximum number of cycles M of the adsorbent to be tested; the evaluation method also includes, for the limit cycle number x 2 The maximum number of cycles M of the adsorbent to be tested is obtained by rounding; specifically, when the limit number of cycles x 2 When it is a positive integer, the maximum number of cycles M of the adsorbent to be tested is equal to the limit number of cycles x 2 equal; when the limit cycle number x 2 When it is a decimal, the maximum number of cycles M of the adsorbent is the limit number of cycles x 2 The integer part in ; the larger the value of M, the greater the maximum number of cycles of the adsorbent to be tested.

[0089] The application of the evaluation method described in the first aspect of the present disclosure in the field of carbon dioxide adsorption.

[0090] The present disclosure is further illustrated by the following examples, but the present disclosure is not limited thereto. The thermogravimetric analyzer used in the present disclosure is STA449F3, manufactured by NETZSCH, Germany. The adsorbent to be tested used in the present disclosure is a self-made adsorbent of Beijing Low Carbon Clean Energy Research Institute.

[0091] Example 1

[0092] Impurity removal treatment: about 10 mg of the adsorbent to be tested is subjected to impurity removal treatment at 115° C. in a nitrogen atmosphere for 30 minutes until the weight of the adsorbent is stable, thereby obtaining an impurity-removed adsorbent;

[0093] S1. Adsorption-desorption test: The nitrogen atmosphere was switched to a mixed atmosphere of nitrogen (85v%) and carbon dioxide (15v%), and the impurity-removing adsorbent was subjected to adsorption treatment at 40°C for 60min until the weight of the impurity-removing adsorbent was stable, thereby obtaining a carbon-rich adsorbent; the mixed atmosphere was switched to a nitrogen atmosphere, and the carbon-rich adsorbent was subjected to regeneration treatment at 100°C for 30min until the weight of the carbon-rich adsorbent was stable, thereby obtaining a regenerated adsorbent. The adsorption-desorption test was repeated 10 times to obtain a thermogravimetric cycle curve.

[0094] S2. Calculate the regeneration rate H of the adsorbent in the i-th adsorption and desorption test according to formula 1 i , in %:

[0095]

[0096] Among them, E 1 is the weight percentage of the adsorbent after desorbing impurities in the first adsorption-desorption test, in wt%; E i is the desorption of CO in the i-th adsorption and desorption test 2 The weight percentage of the adsorbent to be tested is expressed in wt%;

[0097] According to formula 2, the adsorption amount change rate I of the adsorbent in the i-th adsorption and desorption test is calculated. i , in %:

[0098]

[0099] Among them, F 1 is the CO adsorbed by the adsorbent to be tested in the first adsorption-desorption test 2 The weight of the adsorbent to be tested is expressed as a percentage of the weight of the adsorbent to be tested, in wt%; F i is the CO adsorbed by the adsorbent in the i-th adsorption-desorption test 2 The weight percentage of the adsorbent to be tested is expressed in wt%;

[0100] S3, obtain the regeneration rate H of each adsorption and desorption test through formula 1 i , and the regeneration rate H in each adsorption / desorption test i and the corresponding number of cycles i to form a first data set; fitting the first data set to obtain a first fitting curve function H i =-0.0035i+0.9965, goodness of fit R 2 is 0.9481; the adsorption amount change rate I during each adsorption-desorption test is obtained by formula 2 i , and the adsorption amount change rate I during each adsorption-desorption test iand the corresponding number of cycles i to form a second data set; fitting the second data set to a mathematical model to obtain a second fitting curve function I i =-0.0455i+0.9741, goodness of fit R 2 is 0.9956;

[0101] S4. According to E 1 、E i 、F 1 、F i , H 2 ,I 2 , one or more of a first fitting curve function and a second fitting curve function to evaluate the performance of the adsorbent to be tested;

[0102] S5, the change J of the regeneration adsorption amount in two adjacent adsorption and desorption tests calculated according to formula 3 i :

[0103] J i =F i-1 -F i ; Formula 3

[0104] The obtained adsorption amount change J i A scatter plot is made with the number of cycles i. It can be seen from the above scatter plot that the outlier appears in the change of the regeneration adsorption amount between the first and second adsorption-desorption tests, J 1 It is 0.68wt%. It is inferred from the above scatter plot that after the first adsorption-desorption test, the adsorbent to be tested is obviously deactivated;

[0105] S6. Calculate the limit cycle number x when the adsorbent to be tested fails completely according to formula 4 2 is 21.41:

[0106] I(i)=0; Formula 4

[0107] According to the number of limit cycles x 2 The maximum number of cycles M of the adsorbent to be tested is defined as 21.

[0108] Example 2

[0109] CO 2 The evaluation method of the cyclic adsorption performance of the adsorbent is the same as that of Example 1, except that the impurity removal treatment time is 60 minutes and the regeneration treatment temperature is 90°C.

[0110] The first fitting curve function H i =-0.0002i 2 +0.004i+0.9949, goodness of fit R 2 is 0.9924; the second fitting curve function I is obtainedi =-0.036i+0.9541, goodness of fit R 2 is 0.9880;

[0111] According to the calculated change J of the regeneration adsorption amount in two adjacent adsorption and desorption tests i From the scatter plot, we can see that the discrete values ​​appear in the change of the regeneration adsorption amount between the first and second adsorption-desorption tests, J 1 It is 0.53wt%. It is inferred from the above scatter plot that after the first adsorption-desorption test, the adsorbent to be tested is obviously deactivated;

[0112] Limiting cycle number x 2 is 26.5, then the maximum number of cycles M is 26.

[0113] According to Examples 1 to 2 of the present disclosure, the present disclosure obtains a thermogravimetric cycle curve by thermogravimetric analysis, and obtains E according to the thermogravimetric cycle curve. 1 、F 1 、E i and F i , and the above parameters are defined in detail; and the regeneration rate of the adsorbent H is calculated by the calculation formula i and adsorption amount change rate I i , and then according to the regeneration rate of the adsorbent H i and adsorption amount change rate I i By fitting the mathematical model and obtaining the first fitting curve and the second fitting curve, a relatively standard evaluation method for evaluating the performance of the adsorbent based on thermogravimetric analysis can be established. According to actual usage, appropriate parameters can be selected to conduct qualitative analysis on a variety of adsorbents. By comparing the qualitative analysis results, the appropriate adsorbent can be selected. The method has a wide range of use and strong applicability.

[0114] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0115] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0116] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A method for evaluating the cyclic adsorption performance of a carbon dioxide adsorbent, characterized in that: The evaluation method includes: S1, subjecting the adsorbent to be tested to a desorption treatment in a thermogravimetric analyzer and then to multiple adsorption and desorption tests to obtain a thermogravimetric cycle curve; S2. Calculate the regeneration rate H of the adsorbent in the i-th adsorption and desorption test according to formula 1 i , in %: Wherein, E1 is the weight percentage of the adsorbent after desorbing impurities in the first adsorption-desorption test, expressed in wt%; E i is the weight percentage of the adsorbent after desorbing CO2 in the adsorbent to be tested in the i-th adsorption and desorption test, in wt%; According to formula 2, the adsorption amount change rate I of the adsorbent in the i-th adsorption and desorption test is calculated. i , in %: Wherein, F1 is the weight percentage of CO2 adsorbed by the adsorbent to be tested in the first adsorption-desorption test, expressed in wt%; F i is the weight percentage of CO2 adsorbed by the adsorbent to the adsorbent to be tested in the i-th adsorption-desorption test, in wt%; S3, the regeneration rate H of all adsorption and desorption tests i and the corresponding number of cycles i to form a first data set; fitting the first data set to obtain a first fitting curve function H i =f(i); the adsorption rate change rate I during all the adsorption and desorption tests i and the corresponding number of cycles i to form a second data set; fitting the second data set to obtain a second fitting curve function I i = f(i); S4, according to E1, E i , F1, F i , H2, I2, one or more of the first fitting curve function and the second fitting curve function to evaluate the performance of the adsorbent to be tested; The i is a positive integer and i≥2.

2. The evaluation method according to claim 1, characterized in that: Step S4 also includes: S41. Evaluate the adsorbent stability of the adsorbent to be tested according to H2 and the first fitting curve function.

3. The evaluation method according to claim 1, characterized in that: Step S4 also includes: S42, evaluating the adsorption stability of the adsorbent to be tested according to I2 and the second fitting curve function.

4. The evaluation method according to claim 3, characterized in that: Step S4 also includes: S43, according to F1 and F i The adsorption capacity of the adsorbent to be tested is evaluated.

5. The evaluation method according to claim 1, characterized in that: The adsorption-desorption test is performed more than 5 times.

6. The evaluation method according to claim 1, characterized in that: The evaluation method further comprises: S5. Calculate the change J of the adsorption amount of the adsorbent to be tested in two adjacent adsorption and desorption tests according to Formula 3. i , in wt%: J i =F i-1 -F i Formula 3 Among them, F i-1 is the weight percentage of CO2 adsorbed by the adsorbent in the i-1th adsorption-desorption test, where i is a positive integer and i≥2; When the change of adsorption amount J i <0, indicating that the adsorption performance of the adsorbent to be tested in the i-th adsorption-desorption test is improved compared with that in the i-1-th adsorption-desorption test; When the change of adsorption amount J i >0, indicating that the adsorption performance of the adsorbent to be tested in the i-th adsorption-desorption test is lower than that in the i-1-th adsorption-desorption test.

7. The evaluation method according to claim 1, characterized in that: The adsorption-desorption test includes: The adsorbent after impurities are removed is contacted with CO2-rich gas at an adsorption temperature for adsorption treatment; until the weight of the adsorbent after impurities are removed is stable, thereby obtaining a carbon-rich adsorbent; The carbon-rich adsorbent is regenerated at a regeneration temperature until the weight of the carbon-rich adsorbent is stable to obtain a regenerated adsorbent.

8. The evaluation method according to claim 1, characterized in that: The evaluation method further includes calculating the limit cycle number x2 when the adsorbent to be tested completely fails according to Formula 4: I(i)=0; Formula 4 The larger the value of x2 is, the longer the ultimate life of the adsorbent to be tested is.

9. The evaluation method according to claim 8, characterized in that: The evaluation method further includes rounding the limit cycle number x2 to obtain the maximum cycle number M of the adsorbent to be tested; the larger the value of the maximum cycle number M is, the larger the maximum cycle number of the adsorbent to be tested is.

10. Use of the evaluation method according to any one of claims 1 to 9 in the field of carbon dioxide adsorption.

Citation Information

Patent Citations

  • Method and kit for adsorbent performance evaluation

    CN102084236A

  • Method for testing thermodynamic parameters of functional material

    CN104897508A

  • Evaluation apparatus for gas adsorbent

    CN108279182A

  • Method and system for evaluating adsorption performance of powdery coke trace organic matter based on entrained flow bed

    CN108982279A

  • Adsorbate gas adsorption mode determination method and device

    CN112014287A

Cited By

  • Method and system for testing silica gel adsorbent

    CN121347345A

  • A method and system for testing a silica gel adsorbent

    CN121347345B